Impact of outpatient specialty pharmacy on medication adherence in post-kidney transplant patients. (3rd September 2019) - Petrosan, Adina; Belfield, Kristen; Cohen, Elizabeth; DelVecchio, Mitchell; Stutsky, Martha
Abstract: Background: Post-kidney transplant patients are initiated on a complicated medication therapy regimen including 6-7 new medications, with each consisting of multiple tablets or capsules. Medication adherence may be difficult due to the complexity of the regimen and non-adherence can lead to an increased risk of rejection. At Yale New Haven Transplant Center (YNHTC), patients are presented with the option to receive their medications through Outpatient Pharmacy Services (OPS), a Yale New Haven Health specialty pharmacy. Aims: The objective of this study is to determine the impact of OPS on patients' medication adherence. Methods: A retrospective, single center, chart review was conducted of 50 patients who received a kidney transplant at YNHTC between January 2017 and June 2017. Exclusion criteria included patients who were actively enrolled in a research study, deceased within one year of transplant, or had incomplete medical records. Refill data of patients' prescribed doses of anti-rejection medications (tacrolimus, cyclosporine, mycophenolate and azathioprine) was manually retrieved from pharmacies. Adherence was assessed by calculating the proportion of days covered (PDC) in a 365-day time period. The adherence rate between each drug class was then averaged. The primary outcome was the relationship between the patient's pharmacy and the adherence rate (PDC). Patients were divided into three groups; patients who use OPS ( n = 26), patients who use both OPS and another pharmacy ( n = 8), and patients who use another pharmacy only ( n = 16). Secondary outcomes included pre-transplant adherence survey, MediSetGo score, and number of post-transplant readmissions (hospital stay greater than 24 hours). Results: PDC ranged between 65.5-100% for OPS (average = 94.8%), 56.5–98.5% for OPS and another pharmacy (average = 83.2%), and 53.5–100% for another pharmacy only (average = 91.8%). The PDC was significantly lower for patients who used OPS and another pharmacy compared to either OPS alone or another pharmacy alone ( p = .045). Secondary endpoints studied, such as third-party payer, pre-transplant adherence survey and MediSetGo score, were not found to be related to the PDC. Conclusions: Use of OPS alone did not impact the one-year medication adherence rate of post kidney transplant patients. However, a patient's medication adherence rate may be related to the use of multiple pharmacies versus one single pharmacy. Further studies to investigate this relationship should be conducted.